2022
DOI: 10.1093/humrep/deac014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and familial risk of premature ovarian insufficiency in the Finnish female population

Abstract: STUDY QUESTION What is the incidence of premature ovarian insufficiency (POI), has the incidence of POI changed over time, and what is the risk of POI among relatives of POI women? SUMMARY ANSWER The incidence of POI increased among females aged 15–19 years from 2007 onwards and decreased in older age groups, and among relatives of women with POI the risk of POI is significantly increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In a recent register‐based study, we found that 15.9% of POI patients had a genetic disorder or congenital malformation. The overall prevalence of Turner syndrome in our study was 5.13% 9 . Among lifestyle‐based risk factors of POI, cigarette smoking has been confirmed to be an independent risk factor for POI in multiple studies 10–12 .…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…In a recent register‐based study, we found that 15.9% of POI patients had a genetic disorder or congenital malformation. The overall prevalence of Turner syndrome in our study was 5.13% 9 . Among lifestyle‐based risk factors of POI, cigarette smoking has been confirmed to be an independent risk factor for POI in multiple studies 10–12 .…”
Section: Introductionsupporting
confidence: 55%
“…The reimbursement is applied by the treating physician at the time of POI diagnosis, regardless of whether the patient initiates HRT treatment at that time or not. The reimbursement criteria and their changes over time have been described in detail in a previous article 2 . These requirements have always been aligned with international diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations